2022
DOI: 10.1038/s41539-021-00118-3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in cortical responses to letter-speech sound stimuli in 8–11 year-old children

Abstract: While children are able to name letters fairly quickly, the automatisation of letter-speech sound mappings continues over the first years of reading development. In the current longitudinal fMRI study, we explored developmental changes in cortical responses to letters and speech sounds across 3 yearly measurements in a sample of 18 8–11 year old children. We employed a text-based recalibration paradigm in which combined exposure to text and ambiguous speech sounds shifts participants’ later perception of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 86 publications
0
10
1
Order By: Relevance
“…Activation during audiovisual processing showed an inverted U-shaped development within the STG and the lateral precentral gyri for children aged 8 years at the first measurement and a linear development for children aged 9 years at the first measurement. Whereas we observed the peak of activation in the STG at around 7.5 years, the peak in activation reported by Romanovska et al (2022) was at a later age, 9.8 years. It is likely that this discrepancy can be explained by the methodological differences between the two studies.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…Activation during audiovisual processing showed an inverted U-shaped development within the STG and the lateral precentral gyri for children aged 8 years at the first measurement and a linear development for children aged 9 years at the first measurement. Whereas we observed the peak of activation in the STG at around 7.5 years, the peak in activation reported by Romanovska et al (2022) was at a later age, 9.8 years. It is likely that this discrepancy can be explained by the methodological differences between the two studies.…”
Section: Discussioncontrasting
confidence: 78%
“…The inverted U-shaped development of VWFA activation to print has also been observed with functional magnetic resonance imaging (fMRI) measurements ( Dehaene-Lambertz et al, 2018 ). Similarly, the left STG and left lateral inferior precentral gyrus show an inverted U-shaped development during audiovisual processing in 8–11-year-old children ( Romanovska et al, 2022 ).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…These experiments have revealed that deviations in the ERP signal, about 200 ms after stimulus onset, correlate with visual-orthographic processing and occur over the left occipital-temporal cortex (Maurer & McCandliss, 2008;Michel et al, 2004;Rossion et al, 2002;Tarkiainen et al, 1999). The findings of this signal have been used to identify the emergence of literacy by measuring the variations in neuronal activity as a function of literacy training in children (Maurer et al, 2006;Romanovska et al, 2022). In addition to the analysis of auditory and visual processing, electrophysiological investigations have determined that ERP signals near 400 ms post stimulus correlate with semantic evaluation (Deacon et al, 2000;Gomes et al, 1997;Holcomb, 1988;Kutas & Hillyard, 1984;Morgan et al, 2020).…”
Section: Neurophysiological Assessments Of Reading Abilitymentioning
confidence: 99%